STRATEGI KOMUNIKASI KEPALA SEKOLAH DASAR NEGERI CIKASUNGKA III KECAMATAN SOLEAR KABUPATEN TANGERANG DALAM MEMBERIKAN PEMAHAMAN PADA ORANG TUA SISWA AKAN PENTINGNYA PENDIDIKAN - Jeffri, Suci Emelsi; Arfah, Muh; Fu’adiah , Qurrotul (PMPP Lembaga Penelitian dan Studi Kebijakan, 2023)
In the 2023/2024 academic year, the total number of students is 431, consisting of 226 male students and 205 female students, divided into 20 study groups. The Cikasungka III State Elementary School has 8 civil servant teachers and 8 honorary teachers for a total of 16 teachers. With the number of teachers at SD Negeri Cikasungka III, problems can be seen, namely the composition of the class is fat and there is a shortage of teachers in the school. This research uses a case study method, because this research aims to observe the communication strategies used by the Principal of SD Negeri Cikasungka III, Solear District, Tangerang Regency in providing students' parents with an understanding of the importance of education. The research design chosen in this research is a case study with a descriptive qualitative approach. The results of this research are: a) Communicating and building trust with the students' parents using repeated methods of conveying messages and using language and speech that make it easier for the students' parents to receive the messages conveyed, including: 1) communication has many stages, so that awareness arises on the part of children and parents, 2) the communication techniques used are persuasive techniques with the hope of increasing awareness of the importance of education; b) The Principal of SD Negeri Cikasungka III increases the solidarity between teachers and parents by approaching students through parent meetings and conveying an understanding of the importance of education for the future of children of compulsory school age